The Dream Machine - Λιναρδής Απόστολος; Κονδύλη Δήμητρα (The Greek Review of Social Research, 2017)
In this paper, we adopt as theoretical background the main rules set up by Metanet, the “Data Documentation Initiative 3”, along with methodological procedures applied during the implementation of the international survey for adult skills (PIAAC) and the recent European research framework aiming at reuse, long-term preservation and archiving of data collected, created or elaborated within the purposes of a research project aiming at the setting-up of an ideal system related to social data. Hence, we attempt to describe an ideal system which will assist users to design and conduct a study as well as its efficient data archiving and administration together with dissemination outcomes, data and related documentation for secondary use.